2011
DOI: 10.3109/15569527.2011.560913
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-α in vitiligo: direct correlation between tissue levels and clinical parameters

Abstract: These findings, albeit limited in significance by the low number of cases and the retrospective nature of the study, confirm a probable role of TNF-α in the pathogenesis of vitiligo. The intensity of TNF-α staining in vitiligo lesions may be worth to be further studied as a biomarker for potentially successful anti-TNF-α treatment of nonsegmental vitiligo in cases refractory to conventional treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 10 publications
2
40
0
1
Order By: Relevance
“…Cases of vitiligo treated with TNF-α inhibitors, although achieving mixed results, have been reported as well (Rigopoulos et al, 2007;Campanati et al, 2010). A recent study has shown that the anti-TNF-α agent etanercept can stop vitiligo progression and induce repigmentation in some cases (Kim et al, 2011). In vitro direct analyses of skin T cells from the margins of vitiliginous skin have shown that polarized type-1 T cells (CD4+ and CD8+), which secrete predominantly TNF-a and interferon-g, are associated with the destruction of melanocytes during active vitiligo (Huang et al, 2002;Wankowicz-Kalinska et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cases of vitiligo treated with TNF-α inhibitors, although achieving mixed results, have been reported as well (Rigopoulos et al, 2007;Campanati et al, 2010). A recent study has shown that the anti-TNF-α agent etanercept can stop vitiligo progression and induce repigmentation in some cases (Kim et al, 2011). In vitro direct analyses of skin T cells from the margins of vitiliginous skin have shown that polarized type-1 T cells (CD4+ and CD8+), which secrete predominantly TNF-a and interferon-g, are associated with the destruction of melanocytes during active vitiligo (Huang et al, 2002;Wankowicz-Kalinska et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is akin to that of other common skin inflammatory disorders such as psoriasis and atopic dermatitis (Taieb, 2012). Moreover, ample evidence suggests that cytokines, particularly tumor necrosis factors (TNFs) play a role in the depigmentation process of vitiligo (Moretti et al, 2002;Namian et al, 2009;Kim et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental evidences have shown a role of tumor necrosis factor (TNF)-a in the pathogenesis of non-segmental vitiligo; in fact, successful treatment of vitiligo with TNF-a inhibitors has been recently reported. 5 Cutaneous depigmentation involves cytotoxic activity of autoreactive T-cells; it was hypothesized that depigmentation can progress when the activity of regulatory T-cells (Treg) is reduced. A reduced percentage of Treg in non-lesional, perilesional, and lesional vitiligo skin was observed through an evaluation by immunoenzymatic double-staining for CD3 and FoxP3.…”
Section: Introductionmentioning
confidence: 99%
“…Some resistant generalized cases were associated with high skin levels of TNF-alpha, and improvement with TNF-alpha inhibitors like etanercept is reported [9]. …”
Section: Introductionmentioning
confidence: 99%